Disparities in functioning from alcohol and cannabis use among a racially/ethnically diverse sample of emerging adults. (1st May 2022) - D'Amico, Elizabeth J.; Rodriguez, Anthony; Tucker, Joan S.; Dunbar, Michael S.; Pedersen, Eric R.; Seelam, Rachana
Abstract: Background: Trajectory studies have consistently shown that alcohol and cannabis (AC) use during emerging adulthood (EA) affect functioning; however, few studies examine whether racial/ethnic disparities may occur at similar levels of use. Methods: We conducted web-based surveys across five waves from mean age 18.3 through 22.6. The sample (N = 2945) is 55% female, 46% Hispanic, 23% Asian, 23% White, 6% multi-racial (MR)/other, and 2% Black. Measurements: Past month substance use was defined as number of days used. Outcomes at age 22.6 included negative consequences, delinquency, physical ailments and health, depression and anxiety, peer relationship functioning, life satisfaction, employment, and education. Results: Compared to White EAs, Hispanic, Asian, and MR/other EAs reported less initial alcohol use; Hispanic and Asian EAs reported less initial cannabis use, whereas Black EAs reported more cannabis use. Greater initial frequency and increased frequency of AC use were associated with poorer outcomes (e.g., worse mental health). In terms of disparities, compared to White EAs, Hispanic EAs reported poorer physical health at the same levels of AC use; Hispanic, Asian, and MR/other EAs reported greater alcohol consequences and delinquency; Black, Hispanic, Asian and MR/other EAs reported lower life satisfaction; and Hispanic and MR/other EAs were less likely to pursue education beyond high school (although Asian EAs were more likely). Conclusions: Findings emphasize that trajectories of AC use during EA are associated with a range of functional outcomes. Disparities in functioning at similar levels of AC use highlight the importance of reaching racially/ethnically diverse EAs with prevention and intervention programming. Highlights: Alcohol and cannabis trajectories in emerging adulthood predicted numerous problems. Frequency of cannabis use was associated with more problems than alcohol use. Non-White participants had more problems than White participants with similar use rates.